Kinetic Parameters of Soil Enzymes and Temperature Sensitivity Under Different Mulching Practices in Apple Orchards - Yaokun Jiang; Huike Li; Meng Liang; Yang Wu; Ziwen Zhao; Yuanze Li; Guobin Liu; Sha Xue (Agronomy)
Soil mulching practices in apple orchards offer an effective solution to combat declining soil quality, restore land productivity, and boost apple yield. The kinetic parameters of soil enzymes, specifically the maximum reaction rate (Vmax) and the Michaelis constant (Km), are critical indicators of enzyme activity, while the temperature sensitivity (Q10) reflects the thermal stability of the enzymatic reaction system. However, the effects of different mulching practices on soil enzyme kinetic parameters and their temperature sensitivity remain poorly understood, and there is no consensus regarding the most effective mulching strategies for soil conservation. To address this gap, we focused on a typical apple orchard ecosystem in the Loess Plateau region and investigated the responses of soil enzyme kinetic parameters and their temperature sensitivity to various mulching practices, including different cover materials, grass species for cover crops, and cover duration. Our results show that, among the mulching practices, both ryegrass (RE) and maize straw significantly enhanced the maximum enzyme catalytic reaction rates (Vmax) and catalytic efficiency (Kcat) of β-glucosidase (BG), N-acetyl-β-glucosaminidase (NAG), and alkaline phosphatase (ALP). In contrast, black fabric (BF) reduced the temperature sensitivity of the enzyme system by decreasing Vmax and Kcat. Among the grass species used for cover, crown vetch (CV) had the most pronounced effect on Vmax, while long-term grass cover was more effective in improving the nutrient utilisation capacity of the soil enzyme system. Overall, maize straw and long-term grass cover were found to be the most effective in enhancing the soil enzyme system’s ability to decompose and utilise substrates efficiently. This study identifies soil nutrients as key factors influencing the temperature sensitivity of enzyme kinetics. Our findings provide a scientific basis for developing and applying orchard conservation practices and offer technical support for selecting and promoting soil management strategies that improve soil quality and contribute to the sustainable development of the apple industry in the Loess Plateau.